Symbolization of city space in contemporary urban prose (Mesopotamia by Serhiy Zhadan and Istanbul: memories and the city by Orhan Pamuk). - Maryniak, Ruslana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose: To characterize the specificity of symbolization of Kharkiv and Istanbul spaces as former capitals, considering the authors’ and national-cultural peculiarities of the city's representation in contemporary Ukrainian and Turkish prose, based on the urbanistic books of Serhiy Zhadan and Orhan Pamuk.Methods: The methodology of work based on certain provisions of the semiotic and structural-linguistic analysis of Ferdinand de Saussure and the ideas of Yuri Lotman on the social and communicative function of the text, regulations on the phenomenon of the “urban text” by Kaya Semih and Taras Voznyak. Comparative analysis of the collection Mesopotamia by Serhiy Zhadan and the novel Istanbul: Memories and the City by Orhan Pamuk let us compare two “urban” works of fiction (in fact local variants — “Kharkiv” and “Istanbul” texts) and define their aesthetic value in the corpus of texts of artistic urbanism, in which appears the image of a myth city.Results: Both Serhiy Zhadan and Orhan Pamuk devoted their works to their favorite cities: this is the space of their permanent residency, labeled with a special magic. Nowadays in art, including literature, the tradition of ambivalent creation of the image of the cities of Kharkiv and Istanbul continues: industrial — commercial — student and scientific center — the first capital (Kharkiv) and the capital of the Empire — the city-prison — “Arena of Dishonor” (Istanbul). Both novels became a search for answers to questions about what forms the true magic of a city, whether it loses its uniqueness when it ceases to be the capital of the state, a center of rapid development, or whether it instead returns to the autochthonous tradition of original existence.Conclusions: In Serhiy Zhadan’s novel the symbolization of Kharkiv’s landscape, the myth city presented in images of the Ukrainian, or rather Slobozhansky, its Mezhyrichia, its Mesopotamia, its original local civilization — between Lopan and Kharkiv — rivers that remember everything, whose shores renew a person, give strength to move on, and simply give happiness.In the work of Orhan Pamuk we have a completely opposite story about Istanbul, the city that has lost its uniqueness after ceasing to be the capital. Here the myth city is the ancient Constantinople, its residents enveloped in overwhelming sadness, hüzün. However, there is a source of vitality here as well — Bosphorus Strait. For the novel’s character Istanbul’s landscape is also embodied in Byzantine ruins, in abandoned quarters where multiculturalism still “lives”.